Religions as Brands: new perspectives on the marketization of religion and sprituality/ edited by Jean-Claude Usunier and Jorg Stolz - "Usunier, Jean-Claude (ed.);Stolz, Jorg (ed.)" (Surrey, 2014)
During the twentieth century, religion has gone on the market place. Churches and religious groups are forced to 'sell god' in order to be attractive to 'religious consumers'. More and more, religions are seen as 'brands' that have to be recognizable to their members and the general public. What does this do to religion? How do religious groups and believers react? What is the consequence for society as a whole? This book brings together some of the best international specialists from marketing, sociology and economics in order to answer these and similar questions. The interdisciplinary book treats new developments in three fields that have hitherto evolved rather independently: the commoditization of religion, the link between religion and consumer behavior, and the economics of religion. By combining and cross-fertilizing these three fields, the book shows just what happens when religions become brands.
Keywords: Religion-Economic aspects